VERDADES EN PARALELO BAJO LA CENSURA: UNA EXPLORACIÓN DEL HÍBRIDO DOCU-FICCIÓN ‘CHICAS DE CLUB’ (1970), DE JORDI GRAU - M i r e n G A B A N T X O U R I A G E R E K A,V a n e s a F E R N Á N D E Z G U E R R A (Fonseca, Journal of Communication, 2023)
In the following paper we look into the ways in which Jordi Grau (1930) navigated the censors to make an innovative film that challenged the established notions of film-making and the audience’s expectations alike